A Critical Review of Floods History in Kuantan River Basin: Challenges and Potential Solutions - Syeda Maria, Zaidi; Akbari, Abolghasem; Wan Faizal, Wan Ishak (Penerbit UMP, 2014)
Kuantan River basin (KRB) is important watershed passing through Kuantan city of state Pahang. Usually, it receives massive precipitation during north east monsoon season start from November to March. Since past years, it is experiencing severe floods with increased frequency by perceiving heavy rainfall, which produces surpass flow rate than river capacity resulting inundation of low- laying or flood plain areas hampered the human social and economic life. KRB has experienced the worst flood events during recent years that caused massive destruction of land use infrastructure, agriculture and irrigation system, loss of lives and properties, which ultimately affect the revenue loss suffered by Government in recovery of survival and loss. The change in climatic condition and anthropogenic activities following change in nature of flood seems occurrence getting more frequent in urbanized areas. The rapid urbanization leads land degradation and deforestation, which result high flow of surface runoff.However, insufficient drainage system and river evolution and its inadequate capacity also irrefutable factors for flood. The determination of this article is to review the ascertaining KRB flooding factors and discuss the existing challenges that are being faced in order to avert the loss from flood catastrophe.